The role of health resort enterprises in health prevention during the epidemic crisis caused by COVID-19 - Adam R. Szromek (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The COVID-19 pandemic has reduced or even temporarily halted tourism worldwide. The lack of tourists has huge consequences not only for the tourism industry, but also for the tourism economy. Health tourism enterprises are also affected by this problem, but their situation is somewhat different from other tourism enterprises, as the relationship of these enterprises with the healthcare system provides an opportunity to continue operations, albeit in a different role than the tourism function. The diagnostic objective of this article is to assess the impact of the pandemic caused by the SARS-CoV-2 virus on the activities of tourism and medical tourism enterprises operating in spa destinations after 12 months of the pandemic situation. The cognitive objective, on the other hand, is to identify the roles that these companies play in reducing the impact of epidemic risks. The article presents the results of the research conducted in 19 tourism and medical companies, covering 115 sanatorium facilities, run in Polish health spas. The results indicate that although their economic situation is difficult, it is at the same time stable. Two reasons in particular stand out: (1) financial support from government anti-crisis programs; and (2) implementation of rapid organizational changes that enable the implementation of epidemiological prevention tasks, relieving the burden on infectious diseases hospitals by operating an isolation center, a vaccination center, or a quarantine facility for asymptomatic patients. This use of tourism infrastructure contributes to promoting it as open innovation in tourism.
Keywords: 650; tourism; management; health resorts tourism; spa; social open innovation; COVID-19